1976
DOI: 10.1038/bjc.1976.37
|View full text |Cite
|
Sign up to set email alerts
|

A critique of the evidence for active host defence against cancer, based on personal studies of 27 murine tumours of spontaneous origin

Abstract: Extensive experience with isotransplants of 27 different tumours (leukaemias, sarcomata, carcinomata), all of strictly spontaneous origin in laboratory bred mice of low cancer strains CBA/Ht and WHT/Ht, has revealed no evidence of tumour immunogenicity. Of approximately 20,000 maintenance transplants, none failed and none regressed; of almost 10,000 carefully observed tumours arising from small or minimal inocula of tumour cells, none spontaneously regressed. The number of injected viable tumour cells required… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
164
0
1

Year Published

1977
1977
2000
2000

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 438 publications
(171 citation statements)
references
References 29 publications
(12 reference statements)
6
164
0
1
Order By: Relevance
“…Evidence of the non-immunogenicity of these tumours appears elsewhere (Peters, 1975;Hewitt, Blake and Walder, 1976). CBA Carcinoma NT has featured in several previous experimental studies Hewitt, Blake and Porter, 1973;Peters and Hewitt, 1974).…”
Section: Methodsmentioning
confidence: 91%
“…Evidence of the non-immunogenicity of these tumours appears elsewhere (Peters, 1975;Hewitt, Blake and Walder, 1976). CBA Carcinoma NT has featured in several previous experimental studies Hewitt, Blake and Porter, 1973;Peters and Hewitt, 1974).…”
Section: Methodsmentioning
confidence: 91%
“…Perhaps these drugs lessened a prostaglandin-induced inhibition of the immune system (Plescia et al, 1975). Although the NC carcinoma is thought to have low immunogenicity (Hewitt et al, 1976) FLU tended to increase the lymphocyte content of tumours . With regard to tumour spread, aspirin is antimetastatic in mice, possibly due to inhibition of platelet aggregation (Gasic et al, 1973).…”
Section: Discussionmentioning
confidence: 99%
“…The NC tumour used is a transplantable adenocarcinoma which originally arose spontaneously in the mammary gland of a WHT/ Ht mouse; it has been passaged subsequently in this inbred strain, and appears to be of low immunogenicity (Hewitt et al, 1976). The mice were injected with 106 NC carcinoma cells into the left flank, as described previously and the tumours wN-ere excised 2-3 weeks later under anaesthesia with ether or, in some experiments, pentobarbitone.…”
Section: Methodsmentioning
confidence: 99%
“…The experiments used material from the serial passage range 115 to 153, over which no changes in the characteristics of the tumour were observed. Previous studies had shown that no resistance against viable tumour cells could be induced by pretreatment of recipient mice with multiple doses of lethally irradiated homologous tumour cells (Hewitt, Blake and Walder, 1976).…”
Section: Methodsmentioning
confidence: 99%